Distribution of Zakat, Infak and Sadaqah Funds (ZIS) Amid the Covid-19 Pandemic Case Study of the National Amil Zakat Agency (BAZNAS) Bandung City - Lutfi Rohmawati; Poy Saefullah Zevender; Latifahturahmah Latifahturahmah; Tasiman Tasiman; Widayanti Widayanti (PT. Publikasiku Academic Solution, 2022)
This research aims to see how far the distribution of zakat, infak and sedekah (ZIS) funds during the covid-19 pandemic at Badan Amil Zakat Nasional (BAZNAS) of Bandung City. This research is study of ZIS review using a case study approach, in this case by looking at and measuring the extent to which zakat, infak and sedekah fund have been distributed by BAZNAS of Bandung City to mustahiq (zakat recipients). This distribution of ZIS during the covid-19 pandemic is certainly different from period before the covid-19 pandemic. This research uses data collection technique, data obtained from BAZNAS of Bandung City as an institution authorized to manage ZIS funds, while secondary data obtained from. libraries, journals, books, etc. All of these data are materials to see how the distribution of ZIS funds during the covid-19 pandemic in Bandung City. The result of the research showed that BAZNAS of Bandung City had distributed ZIS funds during the covid-19 pandemic included: (1) bantuanlangsungtunai; (2) bantuan modal usahamikro; dan (3) bantuanpaketsembako.